Pengaruh Media Pop-Up Book terhadap Kemampuan Membaca Cerita Pada Pembelajaran Bahasa Indonesia Siswa Kelas II di UPT SDN Ujan Mas, Kecamatan Sungai Are: Studi Kuasi-Eksperimen - Susanti, Livia; Yumarni, Asmara; Astuti, Dina Putri Juni (Yayasan Sembilan Pemuda Indonesia, 2025)
This study aims to test the effect of using pop-up book media on the story reading ability of second-grade students at UPT SDN Ujan Mas, Sungai Are District. The method used is a quasi-experiment with a Quasi-Experimental Design. The study population includes all second-grade students in the 2025 Academic Year, with samples selected through proportional sampling, resulting in class II B as the experimental group and class II A as the control group. Data collection was carried out through observation, interviews, documentation, and reading ability tests. Data analysis used normality, homogeneity, and *t* tests. The results showed that the average post-test score of the experimental class (81.71) was higher than the control class (73.1). The paired t-test strengthened this finding with a *sig. (2-tailed) * value of 0.000 (<0.05), proving that pop-up book media has a significant effect on improving story reading ability. The novelty of the study lies in the application of interactive media in Indonesian language learning in elementary schools. The contribution of this study provides empirical evidence that pop-up books are effective in improving student literacy. The implications of these findings encourage teachers to use creative media in learning to improve students’ reading skills.